1988
DOI: 10.1002/yea.320040208
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity of alcohol dehydrogenase from the yeast Hansenyls polymorpha CBS 4732 and Candida utilis CBS 621

Abstract: The substrate specificity of alcohol dehydrogenase (ADH) from Hansenula polymorpha and Candidu utilis has been compared with that of the classical ADH from baker's yeast. Cell-free extracts of H. polymorpha and C. utiiis exhibited a much higher ratio of butanol to ethanol oxidation than baker's yeast ADH. This was also observed with the purified enzymes. The ratio ofactivities with ethanol and butanol was pH-dependent. With the baker's yeast enzyme the activity strongly decreased with increasing chain length, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…NAD-dependent alcohol dehydrogenases (ADH; EC 1.1.1.1) are widely distributed in nature (Sund and Theorell 1963;Brfind~n et al 1975) and draw considerable attention, amongst others for phylogenetic reasons (Duester et al 1986). In general, these enzymes possess a low affinity, if any, for methanol (e. g., Steinbiichel and Schlegel 1984;Rella et al 1987;Sheehan et al 1988;Verduyn et al 1988). One example is the NAD-dependent alcohol dehydrogenase from Bacillus stearothermophilus DSM 2334 Dowds et al 1988) with apparent Km values for methanol and ethanol of 20 mM and 82 gM, respectively.…”
mentioning
confidence: 99%
“…NAD-dependent alcohol dehydrogenases (ADH; EC 1.1.1.1) are widely distributed in nature (Sund and Theorell 1963;Brfind~n et al 1975) and draw considerable attention, amongst others for phylogenetic reasons (Duester et al 1986). In general, these enzymes possess a low affinity, if any, for methanol (e. g., Steinbiichel and Schlegel 1984;Rella et al 1987;Sheehan et al 1988;Verduyn et al 1988). One example is the NAD-dependent alcohol dehydrogenase from Bacillus stearothermophilus DSM 2334 Dowds et al 1988) with apparent Km values for methanol and ethanol of 20 mM and 82 gM, respectively.…”
mentioning
confidence: 99%
“…Recombinant expression systems of C. utilis or ADH deWcient S. cerevisiae strains might be useful for further characterization of C. utilis ADH1 [10,21]. A previous report of C. utilis ADH enzymes mentioned that at least three ADH isozymes were present in the puriWed preparation [12]. The genetic information of C. utilis ADH1 is helpful for the isolation and analysis of additional ADH genes of C. utilis.…”
Section: Expression and Characterization Of C Utilis Adh1mentioning
confidence: 97%
“…ADH2, a secondary ADH, was fourfold more active on 2-propanol than ethanol [19]. It was reported that puriWed C. utilis ADH enzymes showed high activities with primary alcohols from ethanol to heptanol, and exhibited appreciable activities with secondary alcohols such as 2-propanol and 2-butanol [12]. Meanwhile, upon the previous study showing that C. utilis ADH probably catalyzed acetate ester synthesis [13], the crude enzyme of C. utilis ADH1 in this study was applied to investigate the ability of ethyl acetate formation from ethanol and acetaldehyde as described by Kusano et al [20], but no activity in ethyl acetate production was observed.…”
Section: Expression and Characterization Of C Utilis Adh1mentioning
confidence: 98%
See 1 more Smart Citation
“…N-16 has at least two NAD-dependent ADHs, one that is constitutively produced and the other induced by methanol (Fujii et al, 1989). NAD-dependent ADHs have also been purified from Hansenula polymorpha, and ADH was reported to reduce formaldehyde to methanol (Verduyn et al, 1988). Although these reports raised the possibility that ADH plays a role in formaldehyde detoxification, there have been no experimental data that demonstrate a physiological role for ADH during growth on methanol using mutant or gene-disrupted strains.…”
Section: 1212) and Nadmentioning
confidence: 99%